Sustainability assessment of rural toilet technology based on the unascertained measure theory - Wu, Simei; Chai, Qing; Liu, Xiaojun; He, Bao-Jie (Frontiers in Environmental Science, 2023)
Upgrading toilets in rural areas is an effective way to protect public health and reduce environmental pollution. Although there are studies on rural toilets, the sustainable performance of rural toilets in developing areas is considerably less understood. The study aims to build a sustainability assessment model of rural toilet technology to support the local government in upgrading rural toilets. The unascertained measure theory is integrated into the model to quantify the sustainability performance of rural toilet technology in three dimensions: economy, service and management, and environment. A case study of Honghai Village, Inner Mongolia, China, is conducted to verify the reliability of the sustainability assessment model. The results indicate that the sustainability performance of the three-compartment septic tank toilet technology is good in Honghai Village. The results are consistent with the situation of the three-compartment septic tank toilets in the village, which verifies the model’s validity. This study can help local government significantly upgrade rural toilets and improve the living standards of rural residents.